Influence Of Branding And Location On RPM Shop Purchase Decision - Nurwahyuni Rizkiani; Ari Arisman; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This research aims to determine the simultaneous and partial influence of branding and location on RPM Shop purchasing decisions. The research methods used in this research descriptive method of analysis with a case study approach. The population studied was 100 respondents. The data collected is secondary and primary data. The data analysis in this study used Multiple Regression Analysis using SPSS software version 26. The results showed that branding and location simultaneously influenced the decision to buy RPM Shop Karangnunggal. Branding partially influenced the decision to purchase RPM ShopKarangnunggal. Location partially affects the decision to purchase RPM Shop Karangnunggal